Surveying the ice thickness of the ice climbing wall using TLS surveying method – case of Mlačca Gorge, Slovenia - Aleš Marjetič; Jan Magyar; Tomaž Ambrožič; Polona Pavlovčič Prešeren (Arctic, Antarctic, and Alpine Research)
Investigating the thickness of ice walls is a formidable pursuit, especially considering the dynamic nature of the environment and the rapid changes in ice conditions. With the use of terrestrial laser scanning (TLS), further compounded by the influence of unfrozen droplets on TLS measurements, this challenge is heightened, because the presence of droplets can adversely affect the accuracy and reliability of measurements. The study aimed to procure 3D models of the artificial climbing wall in Mlačca Gorge, Slovenia, to help climbers in charting diverse climbing routes prior to ascent. Concurrently, the research endeavor sought to deepen our understanding of TLS application in demanding icy terrain. This study unveils the outcomes of successive TLS measurements conducted during the winter of 2021, marked by the most significant thickening of the ice wall in the previous four years. Notably, the terrestrial surveys unveiled the pivotal influence of the laser scanner’s wavelength on beam reflectivity, in addition to the consequential roles played by the angle of incidence of the laser beam on the ice wall and atmospheric moisture concentration in the gorge.